Making the Case for Hyperosmolar Saline Arthroscopic Irrigation Fluids: A Systematic Review of Basic Science, Translational, and Clinical Evidence - Oladeji, Lasun O.; Stoker, Aaron M.; Kuroki, Keiichi; Stannard, James P.; Cook, James L. (The Journal of Knee Surgery, 2023)
Commonly used isotonic arthroscopic irrigation fluids, such as normal saline or lactated Ringer's, were initially formulated for intravenous administration so they do not replicate the physiologic properties of healthy synovial fluid. Synovial fluid plays an important role in regulating joint homeostasis such that even transient disruptions in its composition and physiology can be detrimental. Previous studies suggest that hyperosmolar solutions may be a promising alternative to traditional isotonic fluids. This manuscript sought to systematically review and synthesize previously published basic science, translational, and clinical studies on the use of hyperosmolar arthroscopic irrigation fluids to delineate the optimal fluid for clinical use. A systematic literature search of MEDLINE/PubMed and Embase databases was performed in accordance with Preferred Reporting Items for Systemic Reviews and Meta-analyses (PRISMA) guidelines. The search phrases were: (“cartilage” AND “hyperosmolar”); (“arthroscopy” OR “arthroscopic” AND “hyperosmolar”). The titles, abstracts, and full texts were screened for studies on hyperosmolar solutions and articular cartilage. Study quality was assessed, and relevant data were collected. A meta-analysis was not performed due to study heterogeneity. A risk of bias assessment was performed on the included translational and clinical studies. There were 10 basic science studies, 2 studies performed in translational animal models, and 2 clinical studies included in this review. Of the basic science studies, 7 utilized a mechanical injury model. The translational studies were carried out in the canine shoulder and equine stifle (knee) joint. Clinical studies were performed in the shoulder and knee. Multiple basic science, translational, and clinical studies highlight the short-term safety, cost-effectiveness, and potential benefits associated with use of hyperosmolar solutions for arthroscopic irrigation. Further work is needed to develop and validate the ideal formulation for a hyperosmolar irrigation solution with proven long-term benefits for patients undergoing arthroscopic surgeries.
Keywords: hyperosmolar; arthroscopic surgery; cartilage; systematic review